Architecture and Phenomenology: Introduction - Brendan O’ Byrne; Patrick Healy (Footprint, 2008)
The implications of philosophical aesthetics in the consideration of architecture have been relatively slight. Part of the reason is the neglect of architecture in the work of Baumgarten, Burke and Kant. Within the discourse of architecture the questions raised for philosophical consideration arising out of practice restricted the area of reflection and investigation. The dominant positions were to become either a version of neo-Kantianism, or a direct re-working of Hegel’s Lectures on Aesthetics. The significance of Kant’s distinction between ‘free’ and ‘dependent beauty’ is analysed, and in consequence the need to philosophically question again the relation of architecture to building, to dwelling and space. For this the question of accessibility as raised in the phenomenological enquiry, in the work of Brentano, Sartre, Bachelard, Merleau-Ponty, and especially Heidegger points to a different route for the appraisal of philosophical and architectural relations which are exhibited in the contributions of the 10 authors to this issue of Footprint.